Distopia e realidade nas redes: percepções do grupo "Handmaid's Tale BR" sobre o contexto sociopolítico e feminista no Brasil - Teixeira, Isadora Severo (2022)
This work aims to understand perceptions about the connection between feminist gender issues and the Brazilian socio-political reality observed by members of a Facebook group linked to The Handmaid's Tale universe. For this, the research problem asks how the exchanges and interactions established in the Facebook group The Handmaid's Tale Brasil reverberate in the perceptions of its members about tensions related to the Brazilian sociopolitical conjuncture and the feminist gender theme? The general objective is to understand how the issues raised in the Facebook group "The Handmaid's Tale Brasil" contribute to the construction of the perceptions that the members of the group make about the socio-political and gender situation under the contemporary feminist Brazilian perspective. And the specific objectives are: to identify and categorize the themes presented by the members of the group regarding The Handmaid's Tale universe, especially those related to socio-political and gender issues experienced by Brazilian society; understand how the group members perceive their socio-political and gender experiences related to the feminist theme; find out how/if the exchanges and appropriations established in the THT BR group enable its members to reflect on socio-political and gender issues experienced in their experiences in the public and private spheres. As a theoretical research contribution, we are mainly based on the nocturnal maps of the mediations of Jesús Martín-Barbero (1987; 1990; 2010), more specifically on the mediation of networks (2010). In addition, Fernando Balieiro (2018), Flávia Biroli, Juan Marco Vaggione, Maria das Dores Campos Machado (2020), Richard Miskolci, Pedro Paulo Gomes Pereira (2018; 2019), among others, will serve as guides for the debate undertaken in relation to the sociopolitical situation of gender in Brazil. From a methodological point of view, we followed the ethnographic perspective from Christine Hine's Internet Ethnography (2000) and Robert Kozinets' Netnography (2014), which included exploratory observation, participant observation, the application of a semi-structured questionnaire in the Facebook group, and conducting seven in-depth semi-structured interviews with the respondents to the questionnaire. Finally, it was observed that the Handmaid's Brasil group is seen as a dialogic, collaborative space that allows associations between what is in the plot of The Handmaid's Tale and the sociopolitical reality of contemporary Brazilian genre. The analysis was divided, based on the perspective of the group members, between gender issues, addressing sexual double standards, gender violence, wage inequality, etc, and sociopolitical tensions, based on the association of religion as a motivation for the propagation of oppressions, lack of public policies on the rights of minority groups, etc.